Ocean's twelve - Soderbergh, Steven, 1963-; Nolfi, George; Clooney, George; Pitt, Brad, 1963-; Damon, Matt.; Zeta-Jones, Catherine, 1969-; Garcia, Andy.; Cheadle, Don.; Mac, Bernie; Roberts, Julia, 1967-; Warner Bros. Pictures (1969- ); Village Roadshow Pictures; et al. (Burbank, CA : Distributed by Warner Home Video, 2005)
Ocean's Twelve reintroduces Ocean and his perfectly trained team of con men. Dividing forces to hit Paris, Amsterdam, and Rome, the heist-meisters move beyond casinos to tackle new objectives, one of which involves stealing a famous painting.
Special features: Theatrical trailer.
Editor, Stephen Mirrione ; music, David Holmes ; costume designer, Milena Canonero ; production designer, Philip Messina.
George Clooney, Brad Pitt, Matt Damon, Catherine Zeta- Jones, Andy Garcia, Don Cheadle, Bernie Mac, Julia Roberts.
MPAA rating: PG-13; language.
DVD, region 1, widescreen presentation; Dolby surround 5.1, Dolby surround stereo 2.0.
Closed-captioned; English or French dialogue with optional English, French or Spanish subtitles.
Keywords: Robbery -- Drama; Films for the hearing impaired; Feature films; Caper films